Correlation of fine needle aspiration cytology with histopathology for thyroid swellings in a tertiary care hospital in South India - C. Pereira; D. Rohan; L. F. Tauro (Сибирский научный медицинский журнал, 2020)
Fine needle aspiration cytology (FNAC) is documented to be a good tool in the diagnosis of thyroid lesions. It has good diagnostic accuracy and is an inexpensive investigation. Although a good instrument it does have its own limitations especially when it comes to distinguishing a follicular adenoma from follicular carcinoma thyroid. Objectives of the study was the evaluation of FNAC in the diagnosis of thyroid lesions by determining its sensitivity, specificity, diagnostic accuracy, positive predictive value and negative predictive value. Material and methods. This is a retrospective study of 580 cases of thyroid swelling admitted to our hospital and undergone thyroidectomy over a period of 5 years from 2015 to 2020. After thyroidectomy, FNAC reports (Bethesda system for reporting) of those patients were collected and were compared and analyzed with the histopathology reports. Category 1 and category 3 cases were excluded from calculation due to uncertainty in reporting. Data were analyzed to calculate the sensitivity, specificity, diagnostic accuracy, positive predictive value and negative predictive value of FNAC. Results. Our study included a total of 580 cases of thyroid swellings. The male to female ratio was 1:18.2 and the median age was 43 years. On FNAC, 428 cases (73.7 %) were benign, 35 cases (6 %) were indeterminate, 39 cases (6.7 %) were follicular neoplasm, 30 cases (5.1 %) were suspicious for malignancy and 34 (5.8 %) were malignant. 14 (2.4 %) cases were unsatisfactory. Cytology report was then compared with histopathological reports. FNAC had a sensitivity of 84.2 %, specificity of 97.2 % and a diagnostic accuracy of 94.5 %. The positive predictive value and negative predictive value were 88.3 and 96 % respectively. Conclusions. FNAC is a more specific than sensitive when distinguishing between benign and malignant lesions of thyroid. It has good diagnostic accuracy and hence should be used in all tertiary care hospitals prior to surgery in diagnosing thyroid lesions.